2019
DOI: 10.3389/fonc.2019.00824
|View full text |Cite
|
Sign up to set email alerts
|

Role of GFI1 in Epigenetic Regulation of MDS and AML Pathogenesis: Mechanisms and Therapeutic Implications

Abstract: Growth factor independence 1 (GFI1) is a DNA binding zinc finger protein, which can mediate transcriptional repression mainly by recruiting histone-modifying enzymes to its target genes. GFI1 plays important roles in hematopoiesis, in particular by regulating both the function of hematopoietic stem- and precursor cells and differentiation along myeloid and lymphoid lineages. In recent years, a number of publications have provided evidence that GFI1 is involved in the pathogenesis of acute myeloid leukemia (AML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 88 publications
(163 reference statements)
1
28
0
Order By: Relevance
“…Moreover, the F2RL3 gene, which encodes a protease-activated receptor that plays a role in blood coagulation, inflammation, response to pain, and cancer, is also highly connected in the network and directly interacts with RARA, which has been associated with increased sensitivity to retinoids in T-cell lymphoma in experimental settings (Wang et al 2017). Other highly connected smoking-DMPs in the network, such as MYO1G, GFI1, CDKN1A, GNG12, and CYP1B1, have been previously reported as smoking-DMPs in other epigenetic studies (Gonseth et al 2016;Steenaard et al 2015;Stueve et al 2017;Wiklund et al 2019) and have also been implicated in cancer (Groth-Pedersen et al 2012;Möröy and Khandanpour 2019;Yao et al 2018) or cardiometabolic diseases (Dempsie et al 2013;Parmar et al 2018). All of them are directly connected to Cd-associated nodes.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, the F2RL3 gene, which encodes a protease-activated receptor that plays a role in blood coagulation, inflammation, response to pain, and cancer, is also highly connected in the network and directly interacts with RARA, which has been associated with increased sensitivity to retinoids in T-cell lymphoma in experimental settings (Wang et al 2017). Other highly connected smoking-DMPs in the network, such as MYO1G, GFI1, CDKN1A, GNG12, and CYP1B1, have been previously reported as smoking-DMPs in other epigenetic studies (Gonseth et al 2016;Steenaard et al 2015;Stueve et al 2017;Wiklund et al 2019) and have also been implicated in cancer (Groth-Pedersen et al 2012;Möröy and Khandanpour 2019;Yao et al 2018) or cardiometabolic diseases (Dempsie et al 2013;Parmar et al 2018). All of them are directly connected to Cd-associated nodes.…”
Section: Discussionmentioning
confidence: 82%
“…Another transcriptional factor that has an impact on chromatin architecture is growth factor independence (GFI1). It has been shown that GFI1 mediates transcriptional repression mainly by recruiting histone-modifying enzymes such as histone deacetylases (HDAC-1–3), histone methyltransferases (EHMT2) or histone demethylases (KDM1A/LSD1/) [ 169 ]. GFI1 promoted the development of gut innates lymphocyte (ILC2).…”
Section: Chromatin Remodelingmentioning
confidence: 99%
“…LSD1i treatment also increased chromatin accessibility and binding of SPI1 and CEBPα at their target Es/promoters 28 . Knockdown by shRNA or treatment with either the irreversible tranylcypromine (TCP)-derivative LSD1i or the reversible LSD1i SP2509 disrupted LSD1-binding to CoREST and GFI1/1B, induce differentiation markers (CD86 and CD11b) and morphologic differentiation, repress colony growth, as well as sensitize AML blast progenitor cells (BPCs) to all-trans retinoic acid (ATRA) 23 , 25 , 29 32 . Co-treatment with LSD1i and cytarabine, DNA hypomethylating agents, or inhibitor of HDACs, FLT3, DOT1L or BCL2, was shown to exert synergistic lethality in AML expressing MLL fusion protein 25 , 30 .…”
Section: Introductionmentioning
confidence: 99%